2020
DOI: 10.3390/plants9040507
|View full text |Cite
|
Sign up to set email alerts
|

Spinach Plants Favor the Absorption of K+ over Na+ Regardless of Salinity, and May Benefit from Na+ When K+ is Deficient in the Soil

Abstract: Two spinach (Spinacea oleracea L.) cultivars were evaluated for their response to deficient (0.25 mmol c L −1 or 0.25 K) and sufficient (5.0 mmol c L −1 or 5.0 K) potassium (K) levels combined with salinities of 5, 30, 60, 90, and 120 mmol c L −1 NaCl. Plants substituted K for Na proportionally with salinity within each K dose. Plants favored K + over Na + , regardless of salinity, accumulating significantly less Na at 5.0 K than at 0.25 K. Salinity had no effect on N, P, and K shoot accumulation, suggesting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 54 publications
11
38
0
Order By: Relevance
“…However, the increase from 0.3 to 3.0 mmol c L −1 in K was enough to show that K tissue accumulation was antagonistic to Na tissue accumulation. These results agree with a previous report that concluded that a 20-fold increase in K from 0.25 to 5.0 mmol c L −1 decreased Na tissue accumulation [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the increase from 0.3 to 3.0 mmol c L −1 in K was enough to show that K tissue accumulation was antagonistic to Na tissue accumulation. These results agree with a previous report that concluded that a 20-fold increase in K from 0.25 to 5.0 mmol c L −1 decreased Na tissue accumulation [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“…The steady and stepwise increase in tissue Cl, which surpassed the increase in tissue Na ( Figure 3 ), indicates that spinach is more efficient in controlling Na than Cl. Increases in both tissue Na and Cl of similar magnitudes have been reported recently when irrigation water contained 90 and 120 mmol c L −1 of NaCl [ 8 ]. Interestingly, the use of saline water containing 120 and 160 mmol c L −1 in this study resulted in Na shoot accumulation of approximately 50–60 g kg −1 , smaller than the 60–70 g kg −1 of shoot Na reported previously [ 8 ] for the same cultivars under 90 and 120 mmol c L −1 of Na.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations